2014
DOI: 10.1167/iovs.14-15732
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Induced Photoreceptor Death in a Feline Model of Retinal Degeneration

Abstract: Development of an ATP-induced feline model of retinal degeneration provides a rapid and effective large-eyed animal model for research into vision restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 66 publications
1
61
1
Order By: Relevance
“…One eye was injected with a 200-lL solution of sterile phosphate-buffered saline (PBS; 0.9%) containing 0.2 M ATP hydrate to induce photoreceptor degeneration (Sigma Pharmaceuticals Ltd., Melbourne, VIC, Australia) and 0.2 mg dexamethasone to reduce inflammation (4 mg/mL dexamethasone; Aspen Australia, Sydney, NSW, Australia). As sham injections carried a slight risk of cataract formation and a comparison of sham injected and uninjected controls had previously found no differences, 22 the fellow eye was the uninjected control.…”
Section: Anesthesia and Intraocular Injection Of Atpmentioning
confidence: 92%
See 4 more Smart Citations
“…One eye was injected with a 200-lL solution of sterile phosphate-buffered saline (PBS; 0.9%) containing 0.2 M ATP hydrate to induce photoreceptor degeneration (Sigma Pharmaceuticals Ltd., Melbourne, VIC, Australia) and 0.2 mg dexamethasone to reduce inflammation (4 mg/mL dexamethasone; Aspen Australia, Sydney, NSW, Australia). As sham injections carried a slight risk of cataract formation and a comparison of sham injected and uninjected controls had previously found no differences, 22 the fellow eye was the uninjected control.…”
Section: Anesthesia and Intraocular Injection Of Atpmentioning
confidence: 92%
“…All four animals were a subset of a larger cohort (n ¼ 19) required for another study 22 Unilateral retinal degeneration was induced in all four animals by using a single intravitreal injection of ATP at a concentration of 11 mM at the retina as previously described. 22,24,25 We have previously found that ATP injection induces a global retinal degeneration with a variable pattern of photoreceptor loss, where the most severely affected inner retina occurs in regions containing fewer residual photoreceptor nuclei. 22,23 Briefly, the procedure was performed under anesthesia induced through a subcutaneous injection of ketamine (20 mg/kg; Ilium Ketamil; Troy Laboratories Pty.…”
Section: Anesthesia and Intraocular Injection Of Atpmentioning
confidence: 99%
See 3 more Smart Citations